2013
DOI: 10.1021/np400222v
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin Inhibits Inflammatory Pain in Mice by Targeting TRPV1, Oxidative Stress, and Cytokines

Abstract: The flavonoid vitexin (1) is a flavone C-glycoside (apigenin-8-C-β-D-glucopyranoside) present in several medicinal and other plants. Plant extracts containing 1 are reported to possess antinociceptive, anti-inflammatory, and antioxidant activities. However, the only evidence that 1 exhibits antinociceptive activity was demonstrated in the acetic acid-induced writhing model. Therefore, the analgesic effects and mechanisms of 1 were evaluated. In the present investigation, intraperitoneal treatment with 1 dose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(118 citation statements)
references
References 47 publications
6
104
0
2
Order By: Relevance
“…Knowing that oxidative stress plays an important role in the pathogenesis of inflammatory processes [20][21][22] and pain maintenance, we evaluated several models in vivo to establish the anti-inflammatory, anti-nociceptive, and antioxidant effects of Riparin B. Our data showed that Riparin B exhibited anti-inflammatory, anti-nociceptive, and antioxidant activities in vivo experimental models.…”
Section: Discussionmentioning
confidence: 92%
“…Knowing that oxidative stress plays an important role in the pathogenesis of inflammatory processes [20][21][22] and pain maintenance, we evaluated several models in vivo to establish the anti-inflammatory, anti-nociceptive, and antioxidant effects of Riparin B. Our data showed that Riparin B exhibited anti-inflammatory, anti-nociceptive, and antioxidant activities in vivo experimental models.…”
Section: Discussionmentioning
confidence: 92%
“…Inhibited production of TNF-a, IL-1b, IL-6, and IL-33 in mice [161]. Lowered the levels of TNF-a, IL-1b, and IL-6 in gamma-irradiated mice [162].…”
Section: Isoliquiritigeninmentioning
confidence: 97%
“…1A) that has been found in medicinal and other plants, such as Vitex negundo seeds (Zhou et al, 2009), Pennisetum millet (Gaitan et al, 1989), mung bean (Cao et al, 2011), Passion flower (Zucolotto et al, 2012, mimosa , Phyllostachys nigra bamboo leaves (Lee et al, 2010), wheat leaves (Moheb et al, 2011), hawthorn (Ma et al, 2010), and chaste tree or chasteberry (Hajdu et al, 2007). Vitexin has recently received increased attention because of its wide range of pharmacological effects including antioxidant Borghi et al, 2013;Kim et al, 2005;Praveena et al, 2013), anticancer (Choi et al, 2006;Papi et al, 2013;Yang et al, 2013;Zhou et al, 2013Zhou et al, , 2009, antiviral (Krcatovic et al, 2008;Li et al, 2002), anti-inflammatory (Dong et al, 2011(Dong et al, , 2013, anti-nociceptive (Borghi et al, 2013;Demir Ozkay and Can, 2013;Gorzalczany et al, 2011), antihypertensive (Je et al, 2014), anti-spasmodic (Gilani et al, 2006;Ragone et al, 2007), and anti-depressant-like actions . In addition, vitexin has neuroprotective effects on both pentylenetetrazole-induced seizures in rats and the neuronal excitotoxicity induced by glutamate (Abbasi et al, 2012;Yang et al, 2014) and ameliorates the memory impairments in rats induced by scopolamine (Abbasi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%